PENGARUH CR, DER, TATO DAN ROA TERHADAP PBV (Studi Pada Sub Sektor Tekstil Dan Garmen Yang Tercatat Di Bursa Efek Indonesia (BEI) Pada Tahun 2014-2018) - Iwan Firdaus; Rosa Monaliza (Jurnal Doktor Manajemen (JDM), 2019)
This research is to determine the effect of current ratio, debt to equity ratio, total asset turnover, and return on assets on price to book value in textile and garment sub-sector companies listed on the Indonesia Stock Exchange in 2014-2018. The population in this research were the textile and garment sub-sector companies listed on the Indonesia Stock Exchange in 2014-2018 that did not experience losses. The sample method with saturated samples and obtained 7 companies as samples. Research data obtained from the Indonesia Stock Exchange. The more appropriate method used is the common effect. Partially it shows that the variable current ratio and return on assets have a positive and significant effect on price to book value, the debt to equity ratio has a negative and significant effect on price to book value, while only the total asset turnover variable has no effect on the firm value, price to book value.